2015
DOI: 10.1021/acs.joc.5b01384
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Redox-Annulation of Cyclic Amines

Abstract: Cyclic amines such as 1,2,3,4-tetrahydroisoquinoline undergo regiodivergent annulation reactions with 4-nitrobutyraldehydes. These redox-neutral transformations enable the asymmetric synthesis of highly substituted polycyclic ring systems in just two steps from commercial materials. The utility of this process is illustrated in a rapid synthesis of (−)-protoemetinol. Computational studies provide mechanistic insights and implicate the elimination of acetic acid from an ammonium nitronate intermediate as the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 104 publications
1
14
0
Order By: Relevance
“…Instead, a concerted elimination of acetic acid through TS07 (Scheme ) takes place, forming the azomethine ylide 4 from the N , O ‐acetal 2 b . Similar transition states have been described for comparable transformations in the past . Within TS07 , the C−O bond is already completely broken (3.39 Å) while the proton transfer is still in progress.…”
Section: Computational Results and Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Instead, a concerted elimination of acetic acid through TS07 (Scheme ) takes place, forming the azomethine ylide 4 from the N , O ‐acetal 2 b . Similar transition states have been described for comparable transformations in the past . Within TS07 , the C−O bond is already completely broken (3.39 Å) while the proton transfer is still in progress.…”
Section: Computational Results and Discussionsupporting
confidence: 70%
“…Carboxylic‐acid‐catalyzed reaction : After establishing the reaction mechanism for the uncatalyzed reaction, we investigated the role of acetic acid as a model carboxylic acid in these transformations. In previous investigations, the catalytic efficiency of AcOH was traced back to either proton‐shuttle mechanisms, or the formation of acetylated N , O ‐acetals, and both effects could also play an important role in these transformations. Scheme summarizes the lowest‐energy pathway for the acetic‐acid‐catalyzed reaction.…”
Section: Computational Results and Discussionmentioning
confidence: 99%
“…Enantioenriched 4-nitrobutyraldehydes (e.g., 129), substrates that are easily obtained in highly enantioenriched form from aldehydes and nitroalkenes by well-established organocatalytic enantioselective methods, undergo enantiospecific redoxannulations with activated cyclic amines such as THIQ (Scheme 67). 120 The addition of 10 equiv of acetic acid is critical in these reactions. The level of diastereoselectivity is dependent on the aldehyde used.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In 2015, Seidel et al reported a regioselective annulation reaction between THIQ 3 and 4-nitrobutyraldehydes 134 under two different conditions. [44] As shown in Scheme 28 the authors screened the reaction of THIQ 3 with a variety of 4-nitrobutyraldehydes 134 in the presence of acetic acid in refluxing toluene. Under these conditions, a scope of compounds 138 were produced via formation of azomethine ylides 137; whereas in the presence of 2-ethylhexanoic acid (2-EHA), in refluxing xylene, it predominantly generated cyclic amines 136 through formation of azomethine ylides 135.…”
Section: Alkylationmentioning
confidence: 99%